Prevalence of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Asymptomatic Infections in 2 Large Academic Health Systems in Wisconsin. (19th August 2020) - Rivera, Frida; Safdar, Nasia; Ledeboer, Nathan; Schaack, Grace; Chen, Derrick J; Munoz-Price, L Silvia
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) asymptomatic infections may play a critical role in disease transmission. We aim to determine the prevalence of asymptomatic SARS-CoV-2 infection at 2 hospital systems in 2 counties in Wisconsin. The SARS-CoV-2 prevalence was 1% or lower at both systems despite the higher incidence of coronavirus disease 2019 (COVID-19) in Milwaukee County.